L’oscurità del reale. Levinas poeta dell’il y a. - Dadà, Silvia (Bollettino Filosofico, 2017)
In his juvenile works, Levinas describes existence without existent through the concept of il y a, and individuates the main access to it in art. Precisely on the ground of this special role that art has, Levinas describes the il y a through the language of poetry, through the verses of Shakespeare and Baudelaire. The publication of Levinas' previously unpublished notes has revealed many poems which Levinas wrote before the philosophical elaboration of the concept of il y a, in many of which he makes use of images and a language which closely resemble those later used in treating the concept of il y a. In my article I make use of the unpublished notes for giving a unitary account of the philosophical theory of the il y a (and, in particular, the aesthetics with which it is bound) in relation to Levinas' poetical works, and contend that it is precisely from these that his later philosophical work takes its bearings.